2018
DOI: 10.1177/1087054718816169
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Receipt of School Services in a National Sample of Youth With ADHD

Abstract: Objective: The objective of the study is to describe the extent to which students with ADHD received school-based intervention services and identify demographic, diagnostic, and impairment-related variables that are associated with service receipt in a large, nationally drawn sample. Method: Parent-reported data were obtained for 2,495 children with ADHD aged 4 to 17 years from the National Survey of the Diagnosis and Treatment of ADHD and Tourette Syndrome (NS-DATA). Results: The majority (69.3%) of students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 29 publications
3
36
0
1
Order By: Relevance
“…The third hypothesis states that scientific literature fails to focus on how to implement CMS in schools, how to support the teachers, and how to overcome possible barriers when implementing the CMS [17]. The results of the present study find support for this hypothesis, as these topics are rarely handled in either psychology/psychiatry or education.…”
Section: Investigation Of Implementation Strategies and Barrierssupporting
confidence: 49%
See 4 more Smart Citations
“…The third hypothesis states that scientific literature fails to focus on how to implement CMS in schools, how to support the teachers, and how to overcome possible barriers when implementing the CMS [17]. The results of the present study find support for this hypothesis, as these topics are rarely handled in either psychology/psychiatry or education.…”
Section: Investigation Of Implementation Strategies and Barrierssupporting
confidence: 49%
“…Previous research has shown that students with ADHD benefit from specific CMS that teachers can use to handle the symptoms of ADHD in the classroom. However, despite this, CMS are currently not used regularly in schools with the result that students often do not receive the support they could have [12,[14][15][16][17][18]. We assumed that this science-practitioner gap exists because of a communication-related science-science gap between the scientific fields of psychology/psychiatry and education.…”
Section: Study Resultsmentioning
confidence: 99%
See 3 more Smart Citations